Kondisi Self Awareness Pada Anak Korban Bullying - Salsa Lutfiah Zahra; Miratul Hayati (JECED : Journal of Early Childhood Education and Development, 2022)
Bullying behavior has a negative impact on victims of bullying, among others, has an impact on low self-awareness, anxiety, fear and even depression, insomnia, difficulty concentrating, not confident, sustainable, meaning that someone who is a victim of bullying will have the potential to become bullying behavior in the future.  The purpose of this study was to determine the condition of self-awareness of children who are victims of bullying.  This study uses a qualitative approach to the phenomenological method.  Data collection was carried out through in-depth interviews with informants, then the data that had been collected was analyzed using Miles Huberman analysis.  This study explains the condition of self-awareness of children who are victims of bullying aged 7-8 years which includes the form of bullying behavior, the impact of bullying behavior and also the condition of self-awareness of children who are victims of bullying behavior.